2017
DOI: 10.1037/fsh0000283
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers in diabetes care: A systematic review of randomized controlled trials.

Abstract: Principal implications relate to the need for more research regarding CHW intervention types and methods, and further investigation about the mechanisms of change within a CHW-delivered intervention. Findings support the case for more CHWs in treatment teams to bridge patients with the medical system. This research will serve to better equip providers in the support of patients managing Type 2 diabetes and advance the Triple Aim of health care. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…That is probably the reason for the scarcity of meta-analysis measuring the impact of interventions aimed to improve NCD management in SSA [ 80 ]. For instance, a recent systematic review on the role of CHWs treating diabetes in the United States [ 81 ] suggests that CHW interventions have significant impact in physical health outcomes. However, similar analysis of the interventions that are currently being developed in SSA would be an important contribution to inform policy makers about effective interventions for the improvement of diabetes care in the region.…”
Section: Discussionmentioning
confidence: 99%
“…That is probably the reason for the scarcity of meta-analysis measuring the impact of interventions aimed to improve NCD management in SSA [ 80 ]. For instance, a recent systematic review on the role of CHWs treating diabetes in the United States [ 81 ] suggests that CHW interventions have significant impact in physical health outcomes. However, similar analysis of the interventions that are currently being developed in SSA would be an important contribution to inform policy makers about effective interventions for the improvement of diabetes care in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Lay community health workers have been used in a variety of primary and community-based health-care settings for the delivery of disease prevention and self-management programs with the added advantage of peer support. [33][34][35] Our study found that the majority of food pantry personnel have adequate health literacy and many have a personal history of food assistance program use and/or a diagnosis with diabetes or hypertension, which makes these individuals ideal candidates for a similar peer support role in food pantry-based health programs. Furthermore, food bank-sponsored trainings for food pantry workers on health-related topics may be a natural extension for many food banks that have traditionally offered pantry personnel training programs, primarily on the topics of food safety [36][37][38] or building agency capacity, 36-39 though some provide nutrition education and healthful food stocking strategies to personnel.…”
Section: Discussionmentioning
confidence: 79%
“…361 Apart from medical care, patients with diabetes with or without CKD may need advice, every now and then, from allied health care professionals, such as nurse educators, registered dietitians, physical trainers, social workers, psychologists, or pharmacists on how to cope with the condition on a daily basis. 362 In some patients with T2D, especially those with social disparity or emotional distress, psychosocial support from peers 363 and community health care workers 364 can also improve metabolic control, emotional well-being, and reduce hospitalizations.…”
Section: Key Informationmentioning
confidence: 99%